ASCT2 (SLC1A5)-Deficient Mice Have Normal B-Cell Development, Proliferation, and Antibody Production - Masle-Farquhar, Etienne; Bröer, Angelika; Yabas, Mehmet; Enders, Anselm; Bröer, Stefan (Frontiers in Immunology, 2017)
SLC1A5 (solute carrier family 1, member 5) is a small neutral amino acid exchanger that is up-regulated in rapidly proliferating lymphocytes, but also in many primary human cancers. Furthermore, cancer cell lines have been shown to require SLC1A5 for their survival in vitro. One of SLC1A5’s primary substrates is the immunomodulatory amino acid glutamine, which plays an important role in multiple key processes, such as energy supply, macromolecular synthesis, nucleotide biosynthesis, redox homeostasis and resistance against oxidative stress. These processes are also essential to immune cells, including neutrophils, macrophages, B and T lymphocytes. We show here that mice with a stop codon in Slc1a5 have reduced glutamine uptake in activated lymphocytes and primary fibroblasts. B and T cell populations and maturation in resting mice were not affected by absence of SLC1A5. Antibody production in resting and immunised mice and the germinal centre response to immunisation were also found to be normal. SLC1A5 has been recently described as a novel target for the treatment of a variety of cancers and our results indicate that inhibition of SLC1A5 in cancer therapy may be tolerated well by the immune system of cancer patients.